Identification of an in vitro artemisinin-resistant Plasmodium falciparum kelch13 R515K mutant parasite in Senegal - Sene, Seynabou D.; Pouye, Mariama N.; Martins, Rafael Miyazawa; Diallo, Fatoumata; Mangou, Khadidiatou; Bei, Amy K.; Barry, Alioune; Faye, Oumar; Ndiaye, Oumar; Faye, Ousmane; Sall, Amadou A.; Lopez-Rubio, Jose-Juan; et al. (Frontiers in Parasitology, 2023)
Emergence of artemisinin resistance (ART-r) in Plasmodium falciparum malaria parasites has substantially compromised the efficacy of antimalarial treatments across southeast Asia. In Africa, sporadic cases of delay in parasite clearance were reported since 2017. The risk of artemisinin resistance emerging or spreading within the African continent will surely jeopardize past progress made in reducing worldwide malaria burden. In collaboration with Institut Pasteur Dakar, Senegalese sentinel surveillance sites, blood samples were collected during the 2018 Dengue outbreak surveillance in Senegal. To investigate ART-r, cases around a malaria symptoms persistence upon 3 days Artemisinin-Based Combination therapies (ACT) treatment case, fifteen blood samples were collected from malaria infected patients. We have identified for artemisinin resistance associated mutation PfKelch13R515K clinical isolate from Senegal central region Kaolack. To overcome collection methods of viable cell lines in the field stations to further confirm the mutation associated phenotype, in vitro testing were carried out with CRISPR-Cas9 genome editing. Standard Ring Survival assay RSA0-3h showed increased in vitro RSA0-3h ART-r phenotype in PfKelch13R515K transgenic lines while PfKelch13R622I a mutant previously associated with delayed in vivo parasite clearance in Ethiopia does not confer elevated RSA0-3h survival. In this article we report for the first time the functional significance of the PfKelch13R515K mutation previously identified in SE Asia in African malaria setting. This work has demonstrated the impact of combined molecular surveillance tool and a complementary Plasmodium falciparum genome editing to assess the functional relevance of single nucleotide polymorphism in pathogen resistance tracking and monitoring. These data do support the National Malaria Control program’s scale up strategic plans against artemisinin and its partner’s drug.